Social media use to improve communication on children and adolescent's health: the role of the Italian Paediatric Society influencers - Elena Bozzola; Anna Maria Staiano; Giulia Spina; Nicola Zamperini; Francesco Marino; Marco Roversi; Giovanni Corsello; The Italian Paediatric Society Executive Board (BMC, 2021)
Abstract Background Fake news on children's and adolescent health are spreading. Internet availability and decreasing costs of media devices are contributing to an easy access to technology by families. Public health organizations are working to contrast misinformation and promote scientific communication. In this context, a new form of communication is emerging social media influencers. Aim of this study is to evaluate the role of paediatric influencers (PI) in communicating information about children and adolescents' health. Materials and methods A group of PI was enrolled from December 2019 to January 2020 by a scientific commission nominated by the Italian Paediatric Society (SIP). PI were asked to share Facebook messages from the official page of the SIP to their own network. Social media tools have been evaluated across 12 months, from July 28, 2019, to July 11, 2020. For the purposes of clarity, we schematically divided the study period as follows: the period of PIs activity (January 6, 2020, to July 11, 2020) and the period when PIs were not yet active (July 28, 2019, to January 4, 2020). Information on Facebook page (lifetime total likes, daily new likes, daily page engaged, daily total reach) and on published post (lifetime post total reach, lifetime post organic reach, lifetime engaged users) were evaluated. Results A significant increase in Facebook daily new likes, page engagement and total reach, as well as in lifetime post total and organic reach was evidenced. As for PI, they reported a positive experience in most cases. Discussion In the digital era, communication strategies are becoming more important, so that the scientific community has to be actively involved in social media communication. Our pilot study demonstrated that the recruitment of paediatric influencers has increased communication and interaction of the SIP Facebook page. Conclusion Our study shows the potential role of influencers: spreading health messages via PI seems to be a successful strategy to promote correct communication about children's and adolescents' health.